Effect of Twin Boundary Density on Mechanical Behavior of Al0.1CoCrFeNi High-Entropy Alloy by Molecular Dynamics Simulation - Zhang, Luming; Xin, Hao; Zhao, Dan; Li, Zhiqiang; Ma, Shengguo (Frontiers in Materials, 2022)
The molecular dynamics simulation method was used to study the influence of co-lattice twin boundary (TB) spacing on the deformation behavior of Al0.1CoCrFeNi high-entropy alloy single crystal under uniaxial tension. Studies have shown that there is a "sensitive distance" between the twin boundaries, and the sensitivity of the two sides to the change of the twin spacing is different, and the influence of the evolution of the deformation mechanism of the different twin spacing is analyzed from the number of defects and the evolution of the dislocation density. In addition, as the distance between twins decreases, the deformation mechanism gradually transformation from dislocation slip accompanied by defects such as stacking faults and secondary twins to a deformation mode of amorphous phase transition. The research aims to provide guidance and reference for the design of high-performance high-entropy alloys.